The origin of eukaryotes - Blackstone, Neil (Henry Stewart Talks, 2016)
Events leading up to eukaryotic cell formation, Evolutionary conflicts, Mediation of conflicts, Surface-to-volume constraints, Endosymbiosis, Mechanisms of metabolic homeostasis, The major features of eukaryotes